2020
DOI: 10.1371/journal.pone.0236166
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among commercial practices and author conflicts of interest in biomedical publishing

Abstract: Recently, concerns have been raised over the potential impacts of commercial relationships on editorial practices in biomedical publishing. Specifically, it has been suggested that certain commercial relationships may make editors more open to publishing articles with author conflicts of interest (aCOI). Using a data set of 128,781 articles published in 159 journals, we evaluated the relationships among commercial publishing practices and reported author conflicts of interest. The 159 journals were grouped acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Specifically, available data indicate that the biasing effects of COI may be magnified when authors and the study itself are funded by the same industry sources [1]. Similarly, an analysis using the approach described in this article has found that author COI rates are associated with certain industry payments to biomedical journals [13]. While a network modelling approach has not yet been used to further explore COI broadly, these findings suggest that such an approach might be quite promising.…”
Section: Circulationmentioning
confidence: 80%
See 1 more Smart Citation
“…Specifically, available data indicate that the biasing effects of COI may be magnified when authors and the study itself are funded by the same industry sources [1]. Similarly, an analysis using the approach described in this article has found that author COI rates are associated with certain industry payments to biomedical journals [13]. While a network modelling approach has not yet been used to further explore COI broadly, these findings suggest that such an approach might be quite promising.…”
Section: Circulationmentioning
confidence: 80%
“…Below we describe the PML parser in more detail. The PML parser will be most readily applicable for other projects in the humanities, and the functionality of the HMA parser is fully explained in [13]. Following the explanation of parser components, we offer a more complicated parsing example.…”
Section: Methodsmentioning
confidence: 99%
“…Although we are aware of studies that evaluate COI magnitude, for example, they were not returned by our search strategy either because they treat COI magnitude in the aggregate 43 or because they assess non-target outcomes such as associations with commercial publishing practices. 44 Additionally, AMC guidelines are designed to respond to COI risks in multiple domains including research, clinical practice and medical education. We assume that COI strata related to industry-funded continuing medical education or pharmaceutical representative access to AMCs are designed primarily to address risks of bias associated with medical education and clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Our review evaluates the methodological design and approaches to variable stratification for studies of the relationships between industry funding or author COI and four specified outcomes of interest in biomedical research. Although we are aware of studies that evaluate COI magnitude, for example, they were not returned by our search strategy either because they treat COI magnitude in the aggregate43 or because they assess non-target outcomes such as associations with commercial publishing practices 44. Additionally, AMC guidelines are designed to respond to COI risks in multiple domains including research, clinical practice and medical education.…”
Section: Discussionmentioning
confidence: 99%
“…The readers of peer‐reviewed manuscripts are more trusting of authors who disclose their conflicts of interest because it can demonstrate both honesty and expertise (Graham et al, 2020). In an attempt to ensure the transparency and quality of the papers they publish, several leading medical and dental journals, including the Journal of the American Medical Association ( JAMA) and the International Endodontic Journal , have adopted a policy of declaring potential sources of conflicts of interest (Fontanarosa & Bauchner, 2017).…”
mentioning
confidence: 99%